Optical IFU spectroscopy of a bipolar microquasar jet in NGC 300 - McLeod, Anna F.; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We recently reported the discovery of a candidate jet-driving microquasar (S10) in the nearby spiral galaxy NGC 300. However, in the absence of kinem
Gesehen am 27.05.2019